Negosiasi Identitas Mahasiswa Papua Dengan Host Culture di Kota Semarang - Nurul Athira Yahya; Turnomo Rahardjo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
The stereotype that has been attached to Papuan students has become a problem for them to show their identity. Negative stigma also appears to the Papuan ethnic group and the impact on Javanese society that still has anxiety to interact with Papuans. Discrimination and racism eventually evolved due to the physical differences that ethnic Papuans and Javanese ethnicity possess. This study aims to describe the experience of identity negotiation by Papuan students with host culture in the city of Semarang. The research method uses qualitative type with phenomenology approach. This research also supported by Cultural Identity Theory and Identity Negotiation Theory of Stella Ting-Toomey. Informants in this study consisted of five Papuan students who had been more than one year studying in Semarang and five host cultures who had been social interaction with Papuan students. The result of the process identity negotiation conducted by Papuan students with host culture in Semarang City showed Papuan students with their curly-hair and black-skinned appearance becoming the first identity recognized by the host culture. Furthermore, the process of identity negotiation is intertwined through interaction with the overt and mingle with the host culture. Questions from host culture is also an opportunity for Papuan students to explain about Papua and their own personal background. Language differences become one of the obstacles experienced by Papuan students to revealed their cultural identity. In addition, the sense of shame possessed by Papuan students is also become a obstacles in the disclosure of identity. As the stereotype develops in society about Papuan students, it is not the main cause that affects the interaction process with host culture. The stereotype only applies to the initial assessment when first meet, as the initial information and this does not apply to the next assessment. Therefore, the process of negotiating the identity of Papuan students with a host culture have a challenge not to the stereotype that develops but in the self-disclosure of Papuan students to revealed their cultural identity.